2022
DOI: 10.1371/journal.pone.0274621
|View full text |Cite
|
Sign up to set email alerts
|

Did Covid-19 lockdown positively affect the urban environment and UN- Sustainable Development Goals?

Abstract: This work quantifies the impact of pre-, during- and post-lockdown periods of 2020 and 2019 imposed due to COVID-19, with regards to a set of satellite-based environmental parameters (greenness using Normalized Difference Vegetation and water indices, land surface temperature, night-time light, and energy consumption) in five alpha cities (Kuala Lumpur, Mexico, greater Mumbai, Sao Paulo, Toronto). We have inferenced our results with an extensive questionnaire-based survey of expert opinions about the environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Hayati et al (2022) reported that the COVID-19 pandemic has decreased the density of marine litter on 90% of the surveyed beaches in Caspian coasts. Also,Nigam et al (2022) observed a low density of litter on all beaches in Goa, India compared to previous estimates, indicating better beach management Filho et al (2023). also observed the highest reduction in total marine litter between the studied periods.…”
mentioning
confidence: 46%
“…Hayati et al (2022) reported that the COVID-19 pandemic has decreased the density of marine litter on 90% of the surveyed beaches in Caspian coasts. Also,Nigam et al (2022) observed a low density of litter on all beaches in Goa, India compared to previous estimates, indicating better beach management Filho et al (2023). also observed the highest reduction in total marine litter between the studied periods.…”
mentioning
confidence: 46%